Iceland : Sixth Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses the recommendations of the Sixth Post-program Monitoring Discussions with Iceland. Iceland recently updated its capital account liberalization strategy. The strategy takes a staged approach, starting with steps to address the balance-of-payments overhang of the old bank estates-prioritizing a cooperative approach with incentives-in a manner consistent with maintaining stability. Growth is accelerating in 2015 and is expected to reach 4.1 percent, backed by significant investment, wage- and debt relief-fueled consumption, and booming tourism. The general government is projected to record a surplus of 0.8 percent of GDP in 2015, helped by large one-offs. Small deficits are also expected over 2016-20.